Cells deficient in base-excision repair reveal cancer hallmarks originating from adjustments to genetic instability - Markkanen, E; Fischer, R; Ledentcova, M; Kessler, B; Dianov, G (Oxford University Press, 2015)
Genetic instability, provoked by exogenous mutagens, is well linked to initiation of cancer. However, even in unstressed cells, DNA undergoes a plethora of spontaneous alterations provoked by its inherent chemical instability and the intracellular milieu. Base excision repair (BER) is the major cellular pathway responsible for repair of these lesions, and as deficiency in BER activity results in DNA damage it has been proposed that it may trigger the development of sporadic cancers. Nevertheless, experimental evidence for this model remains inconsistent and elusive. Here, we performed a proteomic analysis of BER deficient human cells using stable isotope labelling with amino acids in cell culture (SILAC), and demonstrate that BER deficiency, which induces genetic instability, results in dramatic changes in gene expression, resembling changes found in many cancers. We observed profound alterations in tissue homeostasis, serine biosynthesis, and one-carbon- and amino acid metabolism, all of which have been identified as cancer cell 'hallmarks'. For the first time, this study describes gene expression changes characteristic for cells deficient in repair of endogenous DNA lesions by BER. These expression changes resemble those observed in cancer cells, suggesting that genetically unstable BER deficient cells may be a source of pre-cancerous cells.